THE INFLUENCE OF TASTE, PRICE AND BRAND IMAGE ON PURCHASE DECISIONS AT THREATENED AYAM RESTAURANTS IN MEDAN - Rilza Yusifa Wanda; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of the study was to determine the partial and simultaneous effect of taste, price and brand image on purchasing decisions at threatened chicken restaurants in Medan. The associative method is used in this study. 114 respondents were the sample in this study. Questionnaires are used as a collection tool as a data collection tool, and the data analysis technique uses multiple linear regression. The results showed that taste proved to have a positive and significant effect on purchasing decisions. Price is proven to have a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Simultaneously there is a positive and significant influence of taste, price and brand image on purchasing decisions with a value of Fcount 69.111> Ftable 2.68.